2021
DOI: 10.1016/j.cegh.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Public perception and preparedness for the pandemic COVID 19: A Health Belief Model approach

Abstract: Background Coronavirus disease 2019(COVID-19) pandemic is recognized as a major threat to human health in 2020. As the disease is new and spreading quickly, the scientific community is reporting new information daily to address this issue. The public is well informed and is ready to adopt the protective and preventive measures suggested by the authorities. Aim & objective This study is aimed at understanding the perception towards the pandemic using the Health Belief Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
198
2
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(256 citation statements)
references
References 10 publications
(9 reference statements)
16
198
2
18
Order By: Relevance
“…The rural respondents were also found to be showing poor social distancing patterns, which has been supported in another study as well ( 52 ). The negative attitudes toward COVID-19 were found to be having a negative influence on the social distancing-related preparedness, as negative attitudes possibly reduced the risk perception of the respondents, which push them to be less prepared ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 97%
“…The rural respondents were also found to be showing poor social distancing patterns, which has been supported in another study as well ( 52 ). The negative attitudes toward COVID-19 were found to be having a negative influence on the social distancing-related preparedness, as negative attitudes possibly reduced the risk perception of the respondents, which push them to be less prepared ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 97%
“…14 Moreover, there was good knowledge on the situation of COVID-19 but poor perceived knowledge on preventive measures. 28 A study conducted in Nepal revealed that the knowledge of people about COVID-19 was high, but there was a gap in knowledge on social distancing and quarantine. There was a positive perception towards universal safety measures of COVID-19, but negative perceptions also existed such as: COVID-19 attacked only older people; and coughing into the elbow was not good practice to prevent the spread of the virus.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Moreover, there was good knowledge on the situation of COVID-19 but poor perceived knowledge on preventive measures. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Cues to action include a diverse range of triggers for individuals to take action and are often divided into internal (e.g., physical symptoms) and external (e.g., mass media campaigns and advice from others) factors [42]. Moreover, such cues include trusted programs from the authorities, events or information from close contacts, the media, and health care providers [8].…”
Section: Cues To Actionmentioning
confidence: 99%